PENERAPAN DATAMINING DENGAN METODE KLASIFIKASI UNTUK STRATEGI PENJUALAN PRODUK DI UD.SELAMAT SELULAR - Sinta Maulina Dewi; Agus Perdana Windarto; Dedy Hartama (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
In the current era of globalization, developments in various fields of business are accelerating. Both in the culinary field and other fields. One of the most sought after business developments is in the field of counters or credit sales. UD.Selamat Selular was founded in 2010, which only has a small shop with no employees to date which has more than 20 employees. This business continues to develop in ever-increasing business competition. Therefore a sales strategy is needed so that it is not inferior to other trading businesses. In this research, it is necessary to test the previous data in order to find out the right sales strategy using Naïve Bayes. The data collection method was conducted by questionnaire and interview with a questionnaire of 160 respondents. From the results of this study it can be concluded that the model formed using the Naïve Bayes algorithm produces an algorithm of 0.650 so that it is classified as Excellent Classification.Keywords: Datamining, Naïve Bayes, Sales Strategy.